Engineering Modular 3D Liver Culture Microenvironments In Vitro to Parse the Interplay between Biophysical and Biochemical Microenvironment Cues on Hepatic Phenotypes. Issue 1 (19th November 2021) - Wang, Alex J.; Allen, Allysa; Sofman, Marianna; Sphabmixay, Pierre; Yildiz, Ece; Griffith, Linda G.
Abstract : In vitro models of human liver functions are used across a diverse range of applications in preclinical drug development and disease modeling, with particular increasing interest in models that capture facets of liver inflammatory status. This study investigates how the interplay between biophysical and biochemical microenvironment cues influences phenotypic responses, including inflammation signatures, of primary human hepatocytes (PHHs) cultured in a commercially available perfused bioreactor. A 3D printing‐based alginate microwell system is designed to form thousands of hepatic spheroids in a scalable manner as a comparator 3D culture modality to the bioreactor. Soft, synthetic extracellular matrix (ECM) hydrogel scaffolds with biophysical properties mimicking features of liver are engineered to replace polystyrene scaffolds, and the biochemical microenvironment is modulated with a defined set of growth factors and signaling modulators. The supplemented media significantly increases tissue density, albumin secretion, and CYP3A4 activity but also upregulates inflammatory markers. Basal inflammatory markers are lower for cells maintained in ECM hydrogel scaffolds or spheroid formats than polystyrene scaffolds, while hydrogel scaffolds exhibit the most sensitive response to inflammation as assessed by multiplexed cytokine and RNA‐Seq analyses. Together, these engineered 3D liver microenvironments provide insights for probing human liver functions and inflammatory response in vitro. Abstract : Human liver models are critical tools in drug development and disease modeling, yet there remains a need for models that better differentiate between healthy and perturbed states. This study presents strategies for engineering perturbation responsive three dimensional human liver models. Modulating the cellular microenvironment using biomaterials and media additives enhances culture function, life‐span, and magnitude of responsiveness to inflammatory stimuli.